Use of whey and molasses as additive for producing silage of Cuba OM-22 (Cenchrus purpureus x Cenchrus glaucum) - Castaño, G. A.; Villa, Lina M. (Cuban Journal of Agricultural Science, 2017)
In order to determine the effect of whey or molasses as additives in the preparation of silages of Cuba OM-22, in the pH, silo temperature during the fermentation and chemical composition of the ensiled material, 128 mini-silages were produced. The experiment lasted 32 d. The treatments had a factorial structure of additive x day. The additive factor consisted of four different additives: a control (C) without additive and other three, where molasses, whey or whey + molasses mixture were used. An amount of 50 mL of additive/kg of fresh material for silage was used. The factor day corresponded to the number of days elapsed between the opening of silage (day 0) and sample-taking. Effect of the additive on the concentration of OM (P=0.0015), CP (P=0.0114), NDF (P <0.0001), NFC (P <0.001) and SE (P=0.0125) was shown. During the fermentation process, CP concentration (P=0.0058) and NDF (P=0.0115) decreased, but that of NFC increased (P <0.0001). There was interaction between additive and day in the pH (P=0.0051) and the temperature of the silo (P <0.0001). The use of the additives has a beneficial effect on forage conservation, which is evidenced with the variation of pH, decrease of NDF and increase of NFC. Variation of pH, when using the mixture of molasses and whey, indicated better fermentation process before the use of these additives separately. Key words: additives, forage preservation, fermentation